Energy and the environment into the 1990s : proceedings of the 1st World Renewable Energy Congress, Reading, UK, 23-28 September 1990 - Sayigh, A. A. M., 1939- (Pergamon, 1990)
As the governments and peoples of the world come to face the global impact of the technological revolution, it is appropriate to consider the future of world energy supplies. This conference approached the task not only of developing the means of tapping renewable energy sources, but also of showing renewable energy to be a viable alternative to current, harmful sources of energy. Economic and educational problems were addressed along with the scientific ones. The development of alternative energy is of no use if it cannot be made economically viable or if people are not convinced of its advantages.